Contribution to the study of the solar Evaporation or Sebkhat El Melah Brine (Tunisia) - M'nif, A; Rokbani, R. (Asian Journal of Chemistry, 2010)
A natural brine coming from Sebkhat EI Melah can be assimilated to a quinary system: Na+, K+, Mg2+, Cl-, SO42- //H2O. The study of the solat evaporation of our raw material can be based on the above-mentioned diagram. The practical crystallisation path is different from the theoretical one; however the recovered salts are similat to the foreseeable ones. Oversaturated solutions and metastable equilibrium may be the origin of the established gap.